2019
DOI: 10.1021/acsami.8b22309
|View full text |Cite
|
Sign up to set email alerts
|

Human Cancer Cell Membrane-Coated Biomimetic Nanoparticles Reduce Fibroblast-Mediated Invasion and Metastasis and Induce T-Cells

Abstract: Biomimetic nanoparticles (NPs) combine the flexibility and reproducibility of synthetic materials with the functionality of biological materials. Here, we developed and characterized biomimetic poly­(lactic-co-glycolic acid) (PLGA) NPs coated with human cancer cell membrane fractions (CCMFs) to form CCMF-coated PLGA (CCMF-PLGA) NPs. We evaluated the ability of these CCMF-PLGA NPs to disrupt cancer cell–stromal cell interactions and to induce an immune response. Western blot analysis verified the plasma membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 36 publications
0
105
0
Order By: Relevance
“…One of the major problems in cancer control is the metastatic ability of the cells. Therefore, the synthesis of drugs and nanomedicines that control this process should be stimulated (Jin et al 2019). Although the involved mechanism is not yet understood, the reduction in migration of MDA-MB-231 cells treated with ruthenium-based metal complexes has been reported (Cao et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major problems in cancer control is the metastatic ability of the cells. Therefore, the synthesis of drugs and nanomedicines that control this process should be stimulated (Jin et al 2019). Although the involved mechanism is not yet understood, the reduction in migration of MDA-MB-231 cells treated with ruthenium-based metal complexes has been reported (Cao et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the density difference between the plasma membrane and other cellular factions, differential centrifugation is mainly used for plasma membrane isolation. However, we found that gradient centrifugation was superior to differential centrifugation in terms of purity of isolated cell membrane fractions (19). Commonly used gradients include discontinuous sucrose, and self-generated Percoll or iodixanol gradients (48,49).…”
Section: Cancer Cell Membranesmentioning
confidence: 91%
“…The RBC membrane was found to act as a nanosponge for toxins, and bestowed a longer circulation pharmacokinetic profile than uncoated NPs (3). Since this initial study, cell membrane coating technology has significantly expanded to the use of membranes from platelets (4)(5)(6)(7)(8) and from nucleated cells, such as macrophages (9)(10)(11)(12), neutrophils (13), beta cells (14), and cancer cells (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The use of cancer cell plasma membranes has attracted attention because these membranes carry tumor-specific receptors and antigens that play a role in cancer cell proliferation, invasion, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…It also successfully traveled to draining lymph nodes post-transdermal injection and facilitated potent tumor-specific immune responses [64]. In another unique nanovaccine design, melanoma cell membrane fractions were coated onto PLGA NPs and their ability to effect fibroblast-mediated invasion, change experimental metastasis, and induce an immune response in immunocompetent mice was evaluated [43]. The nanovaccine successfully inhibited cancer cell migration toward fibroblasts, significantly decreased metastatic burden, and increased cytotoxic T lymphocytes, indicating membrane-wrapped nanovaccines not only show potential as antigen delivery vehicles for primary tumor elimination, but also as metastasis inhibitors.…”
Section: Immune Stimulationmentioning
confidence: 99%
“…Cancer cells are robust and easy to culture in large volumes in vitro for mass membrane collection and also possess the unique ability to self-target homologous cells (also known as homotypic targeting), unlike most other membrane donors [8,9,40,42]. This unique ability translates to cancer cell membrane-wrapped NPs (CCNPs), which retain the ability to homotypically target primary tumors and metastatic nodules [40,[42][43][44][45] ( Figure 2). Additionally, CCNPs display unprecedented binding and selective uptake in tumor cells matched to those from which they were derived, as well as have reduced immune clearance after systemic administration compared to non-coated NPs [22,40,42,44,46,47].…”
Section: Introduction To Cancer and Nanomedicinementioning
confidence: 99%